2010
DOI: 10.1111/j.1468-1293.2009.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV and people over 50 years old in Europe

Abstract: Objective The aim of the study was to report on HIV and older people in the European Region, including new data stratified by subregion and year. Methods Data were collected from the 2008 World Health Organization Regional Office for Europe, Communicable Diseases Unit survey on HIV/AIDS and health systems. Results It was found that 12.9% of newly reported cases of HIV infection in Western Europe in 2007 were in people aged 50 years or older. In Central Europe, almost one‐in‐10 newly reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 22 publications
1
46
1
4
Order By: Relevance
“…Alguns pesquisadores ainda afirmam que a população mais velha, pode não ser percebida por seu médico como em estado de risco de infecção por HIV e, consequentemente, tem menos probabilidade de ser encaminhada para a realização de sorotestagem, para a pesquisa da doença em comparação com os adultos mais jovens. Outro fator a ser considerado, é que quando o teste para HIV é realizado no paciente mais idoso, o diagnóstico é muitas vezes feito mais tarde na história natural da doença, o que aumenta o risco de infecções oportunistas e transmissão a outros parceiros (21) . A literatura enfatiza que, com companheiro fixo, os riscos de exposição ao vírus HIV diminuem, tendo em vista que a multiplicidade de parceiros constitui um fator de risco para o contágio de DST e HIV/AIDS (22) .…”
Section: Discussionunclassified
“…Alguns pesquisadores ainda afirmam que a população mais velha, pode não ser percebida por seu médico como em estado de risco de infecção por HIV e, consequentemente, tem menos probabilidade de ser encaminhada para a realização de sorotestagem, para a pesquisa da doença em comparação com os adultos mais jovens. Outro fator a ser considerado, é que quando o teste para HIV é realizado no paciente mais idoso, o diagnóstico é muitas vezes feito mais tarde na história natural da doença, o que aumenta o risco de infecções oportunistas e transmissão a outros parceiros (21) . A literatura enfatiza que, com companheiro fixo, os riscos de exposição ao vírus HIV diminuem, tendo em vista que a multiplicidade de parceiros constitui um fator de risco para o contágio de DST e HIV/AIDS (22) .…”
Section: Discussionunclassified
“…Lazarus et al found that in 2007, 12.9% and 3.7% of newly reported HIV cases in Western and Eastern Europe, respectively, occurred in people aged 50 years or more. In Central Europe, around one in 10 newly reported HIV cases occurred in people aged 50 years or more 8 . In the United States, the AIDS incidence rate in the population aged 65 or above is approximately 1.60 per 100,000 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…This trend is likely to be the result of: An increased number of people seroconverting at an older age and increasing life expectancy among people living with HIV (PLHIV) on antiretroviral therapy (ART) [1][2][3]. A recent publication from the European Centre for Disease Prevention and Control shows significantly increasing trends in new HIV diagnoses among people aged 50 and older in the European Union and European Economic Area (EU/EEA).…”
Section: Introductionmentioning
confidence: 99%